PENGARUH IKLAN LAYANAN MASYARAKAT HEMAT LISTRIK PT. PLN TERHADAP SIKAP MASYARAKAT DALAM PENGGUNAAN LITRIK DI KELURAHAN WATTANG KECAMATAN POLEWALI - Sri Yuyun; Masyhadiah Masyhadiah; Imra Imra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
This study aims to determine the effect of electricity saving public service advertisements on community attitudes in the Wattang Subdistrict, Polewali District. This type of research uses a quantitative paradigm with a descriptive approach. The results showed that PT. PLN influences the attitude of the community in the use of electricity in the District of Wattang Polewali District influences the attitude of the community. This is based on the number of responses obtained from 100 respondents. It is also known that the three elements of attitude namely cognitive, affective, and conative have an influence on community attitudes in Wattang Sub-District, Polewali District.